Hubungan Tingkat Pengetahuan Perawat Tentang Mobilisasi Dini Dengan Pelaksanaan Tindakan Mobilisasi Dini Pada Pasien Post Operasi - Zainudin Nurkholis; Moh Alimansur (coba, 2013)
Early Mobilization is an effort to maintain independent more early by guiding the patient to maintain physiological function, however they are many afraid to move after surgery, though early mobilization is uppermost factor in quickening to cure of post surgery and can prevent surgical complication. Knowledge and execution in giving nursing mobilization upbringing very early needed in processing dignification and prevention of complication after surgery. This research aim to know that there is relation between knowledge of nursing about early mobilization with early mobilization action at patient post operation or not. The desain research is used correlation method cross sectional approach, the population of this research is laboring nursing in Dahlia Room Hospital of HVA Toeloengredjo Pare that here amount 13 responden have saturate sampling technique so that obtained 13 sample responden. The result of research knowledge of nurse about early mobilization almost knowledgeable entirely goodness (77%), while execution of early mobilization action at post operation patient almost precisely (77%). Pursuant to statistical test of Spearman'S Rank obtained coefficient correlation coefficient of r = 0,595 and in signifikan level p = 0,032. The result of relation degree have known by there are relation which is substansial between level knowledge of nursing about early mobilization with execution of early mobilization action at patient of post operation for that. The nurse expected to skill in early mobilization become more precise again. Keyword : Knowledge, Action, Nurse, Early Mobilization.